2022
DOI: 10.3390/jmse10060813
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Added Resistance and Seakeeping Performance of X-Bow and Wave-Piercing Monohull in Regular Head Waves

Abstract: Bow shape has been recognized as an important factor influencing the seakeeping performance and added resistance of ships. This paper presents a numerical comparative study on added resistance and seakeeping of model ships with ‘X-bow’ and a wave-piercing monohull in regular head waves using a computational fluid dynamics (CFD) software. Different wave heights, wavelengths and forward speeds are considered in the systematic investigation in order to characterize the added resistance and wave-induced motions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Simanjuntak et al, [4] employed Ulstein axe-bow model on Pioneer ship 750 DWT and obtained the total ship's resistance decreased by 4.85% in the deep-water condition with h/t=19.3. Furthermore, Chen et al, [5] reported that the added ship's resistance in the waves condition with the axe-bow is smaller than the wave-piercing bow at the same forward speed. In particular, the investigation on predicting the total ship's resistance using the experimental model test for the validation purposes of numerical models is much recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Simanjuntak et al, [4] employed Ulstein axe-bow model on Pioneer ship 750 DWT and obtained the total ship's resistance decreased by 4.85% in the deep-water condition with h/t=19.3. Furthermore, Chen et al, [5] reported that the added ship's resistance in the waves condition with the axe-bow is smaller than the wave-piercing bow at the same forward speed. In particular, the investigation on predicting the total ship's resistance using the experimental model test for the validation purposes of numerical models is much recommended.…”
Section: Introductionmentioning
confidence: 99%